Interaction between the stage of chronic kidney disease and diabetes mellitus as factors associated with mortality in chronic kidney disease patients: An external cohort study - Laura E. Villegas Sierra; Melisa Buriticá Agudelo; Carlos Enrique Yepes Delgado; Yanett Marcela Montoya Jaramillo; Fabián Jaimes Barragan (Nefrología (English Edition), 2022)
Introduction: Diabetic kidney disease is the main cause of chronic kidney disease (CKD) worldwide. Both CKD and diabetes mellitus (DMT2) are important risk factors for mortality. However, it is still unknown if the risk of death is modified by the simultaneous presence of these diseases. Objective: To evaluate the presence of an interaction between DMT2 and CKD for mortality in a representative population of a Latin American country. Methods: It is an analytical cohort study of patients with CKD, who were followed for 4 years (between 2004 and 2009). We calculated the incidence rate, progression, survival (using Kaplan–Meier curves), interaction (on the additive and multiplicative scales) and impact of the different stages of CKD in patients with and without DMT2 (using a cox proportional hazards model). Results: In this population of 5663 individuals, both DMT2 and CKD are risk factors for mortality (p < 0.001). We found a statistically significant difference in mortality between individuals with and without DMT2, who also had CKD stages 3–4 –5 (Log-rank p = 0.0076). Additionally, we found a statistically significant interaction for mortality in both the additive and multiplicative scales between DMT2 and CKD (p = 0.005). DMT2 was found to be a risk factor for mortality (Hazard Ratio 1.61 p < 0.001), but in individuals with DMT2, the only risks significantly associated with mortality, were age, dyslipidemia and nephroprotective drugs. Conclusión: The interaction between CKD and DMT2 negatively modifies the risk of death of both diseases. This means that when the two diseases are present, the risk of mortality is lower than expected. Resumen: Introducción: La enfermedad renal diabética es la principal causa de enfermedad renal crónica (ERC) en el mundo y tanto la diabetes mellitus (DMT2) como la ERC son importantes factores de riesgo para mortalidad. Sin embargo, se desconoce si la presencia simultánea de ambas enfermedades modifica el riesgo de muerte. Objetivo: Evaluar la presencia de interacción entre DMT2 y estadio ERC respecto a la mortalidad en una población representativa de un país latinoamericano. Métodos: Estudio analítico en dos cohortes de pacientes con diagnóstico de ERC con cuatro años de seguimiento entre 2004 y 2008. Se calculó la tasa de incidencia, progresión, supervivencia (Kaplan-Meier), interacción (aditiva y multiplicativa) e impacto de la presencia de los diferentes estadios de ERC en pacientes con y sin DMT2 mediante un análisis de riesgos proporcionales de Cox. Resultados: En esta población de estudio de 5.663 pacientes, tanto la DMT2 como el estadio de ERC son factores de riesgo para mortalidad (p < 0,001). La diferencia en la supervivencia entre diabéticos y no diabéticos en estadios 3 – 4 – 5 fue estadísticamente significativa (Log-rank p = 0,0076). Se encontró una interacción estadísticamente significativa en las escalas aditiva y multiplicativa entre la presencia de DMT2 y el estadio de ERC, con respecto a la mortalidad (p = 0,005). Se confirmó el impacto de la diabetes como factor de riesgo de mortalidad (Hazard Ratio 1,61 p < 0,001), pero en los pacientes con DMT2 solamente la edad, la dislipidemia y los nefroprotectores estuvieron asociados significativamente con la mortalidad. Conclusión: La interacción entre ERC y DMT2 modifica de forma negativa el riesgo de muerte de ambas enfermedades. Es decir que el efecto conjunto observado es menor al esperado.